A PROCEDURE FOR TUBE COUNT DETERMINATION IN SINGLE AND MULTIPLE PASS TUBULAR HEAT EXCHANGERS - Medeiros, M. S.; Leiroz, A. J. K. (Revista de Engenharia Térmica, 2005)
The development of a simple computational procedure that allows the precise determination of important parameters for the thermal and mechanical design of tubular heat exchangers is discussed in the present work. The design of tubular heat exchangers for a wide variety of applications can involve the use of empirical expressions and data tables for the determination of the tube bundle parameters, such as the tube count and the tube bundle outside diameter. The motivation for developing the discussed procedure resides in addressing cases for which empirical expressions are inapplicable or data table are unavailable. Initially, the shell positions in which tubes can be placed are determined based on specified tube pitch, angle of arrangement, inlet and outlet nozzle diameters and tube bundle-to-shell clearance. The maximum number of tubes for the given configuration is obtained from the tube position searching procedure. A sorting algorithm, based on the tube distance to the shell center, is used to appropriately place a specified number of tubes within the heat exchanger cross section. Results for a single- and multiple-pass fixed-tubesheet heat exchangers are presented and compared with available tube count tables.